2016
DOI: 10.1007/s11515-016-1416-0
|View full text |Cite
|
Sign up to set email alerts
|

Modeling axonal defects in hereditary spastic paraplegia with human pluripotent stem cells

Abstract: BACKGROUND Cortical motor neurons, also known as upper motor neurons, are large projection neurons whose axons convey signals to lower motor neurons to control the muscle movements. Degeneration of cortical motor neuron axons is implicated in several debilitating disorders, including hereditary spastic paraplegia (HSP) and amyotrophic lateral sclerosis (ALS). Since the discovery of the first HSP gene, SPAST that encodes spastin, over 70 distinct genetic loci associated with HSP have been identified. How the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 117 publications
0
13
0
Order By: Relevance
“…However, SPAST mutations leading to an HSP phenotype display a dying-back axonopathy of the affected neurons, especially the corticospinal MNs. Moreover, such axon abnormalities have been identified in iPSC-derived neurons (Denton et al, 2014(Denton et al, , 2016, which are known to be a powerful tool to study human neurons in vitro.…”
Section: Spastin (Spast)mentioning
confidence: 99%
“…However, SPAST mutations leading to an HSP phenotype display a dying-back axonopathy of the affected neurons, especially the corticospinal MNs. Moreover, such axon abnormalities have been identified in iPSC-derived neurons (Denton et al, 2014(Denton et al, , 2016, which are known to be a powerful tool to study human neurons in vitro.…”
Section: Spastin (Spast)mentioning
confidence: 99%
“…The potential of iPSC to generate a patient-specific cell model that represents the cell type affected by the disease of interest with the same genetic background opened new possibilities to study MND in a human neuronal cell culture model (reviewed in Denton et al, 2016). For example, analysis of SPAST-deficient neurons generated from SPG4 patients revealed pathophysiological axonal defects like axonal swellings, a hallmark of HSP disease pathology, in human iPSC-derived neurons (Havlicek et al, 2013;Denton et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research using stem cell models to study HSP disease pathogenesis, including SPG4 (HSP- SPAST ), SPG3A (HSP- atlastin-1 ), and SPG11 (HSP- spatacsin ) (5–7), have revealed several potential treatment options targeting the underlying disease mechanisms (8). There is a paucity of clinical trials for HSP drug treatment options, the most recent trials targeting SPG5 (HSP- CYP7B1 ) showed improvement of biological markers but no discernible clinical improvement (1, 9, 10).…”
Section: Introductionmentioning
confidence: 99%